Taking stock of the availability and functions of National Ethics Committees worldwide - Hummel, Patrik; Adam, Taghreed; Reis, Andreas; Littler, Katherine (BMC Medical Ethics, 2021)
Background National Ethics Committees (NECs) offer important oversight and guidance functions and facilitate public debate on bioethical issues. In an increasingly globalized world where technological advances, multi-national research collaborations, and pandemics are creating ethical dilemmas that transcend national borders, coordination and the joining of efforts among NECs are key. The purpose of this study is to take stock of the current NEC landscape, their varying roles and missions, and the range of bioethical topics on which they deliberated since their inception. Methods Data on the availability, functions, and ethical deliberations (publications) of NECs globally were gathered through a systematic search of NEC websites and through contacts known to the authors. The search was conducted in English, French, and Spanish. The data abstraction was done in Excel and included the NEC’s country, region, functions, and deliberations on bioethical issues. Deliberation topics were classified into thematic categories through an iterative process of regrouping to arrive at the main set of themes. Results 124 NECs in 100 countries were identified. 44% of the NECs are in Europe and 47% are in high-income countries. Out of the 1108 retrieved publications, 40% were on bioethics in the context of research, followed by the clinic (28%) and public health issues (22%). The top five topics of these publications were: research ethics (124; 9%), genetics and genomics (62; 6%), organ transplantation (58; 5%), assisted reproductive technology (49; 4%), and end of life (36; 3%). Conclusion Our study makes an important contribution to understanding the current interests and functions of NECs and the range of their bioethics deliberations. By making the data publicly available through this publication, it allows users to conduct tailored analyses and queries based on their interests, and to seek and strengthen collaboration and exchange. It also makes the case for the fruitfulness of developing and maintaining a global repository of current and new deliberations to more effectively advance this field for the greater good of humanity, research, and public health.<br
Keywords: National Ethics Committees; Research ethics; Medical ethics; Public health ethics; Health policy; Global bioethics; Deliberation